Flexible piezoelectric energy harvester - Ab. Aziz, Ali Hussaini; Ahmad Hafizullah, Anis Salsabila; Abdullah, Shahino Mah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
We produce energy in each of our steps, and in this project, that energy can be measured and used for benefit. This project mainly focuses on the use of a 3D-printed insole for shoes. A piezoelectric film device is integrated into the insole’s vital points including the heel, the ball, and the middle of the foot. The piezoelectric film device is made with Polyvinylidene fluoride (PVDF) strips that are less than one millimetre in thickness to provide comfort to users as well as generating energy while walking. The design of the insole is customizable for the best comfort of users. Each capacitance and voltage produced by the steps can be measured by using a standard LCR meter. This project has promising potential for the sustainable energy production in many ways. The insole can also be applicated into healthcare uses, where we can determine the most efficient way to take a step. With an appropriate patent protection, regulatory compliance, and partnerships, this technology can benefit medical facilities, everyday safety, and a cleaner tomorrow.